The ‘Day After’ Islamic State: Scenarios for Southeast Asia - Singh, Bilveer (2016)
While the self-styled Islamic State (IS) is losing some of its territories in Syria and Iraq to the western-led coalitions new dangers are emerging with its ideological spread worldwide. Many Southeast Asian fighters supporting IS may return to launch attacks on home soil.